A high‐efficiency 50 W X‐band GaN power amplifier in hybrid MIC technology. Issue 2 (30th November 2020) - Ahmadi, Amirhossein; Moazzen, Hamidreza; Karimzadeh Baee, Roghieh; Sardrood, Parvin Sojoodi
Abstract: In this paper, the design, fabrication, and measurement results of a two‐stage X‐band highly efficient 50 W power amplifier are presented. In the design approach, two 0.25 μm bare‐die GaN on SiC transistors, where one of them has the largest gate periphery on the market, are chosen. A considerably high saturated power gain of more than 20 dB and better than 40% power‐added efficiency (PAE) are achieved over the 10.9 to 11.1 GHz bandwidth. Modulated measurements demonstrate an average output power of 40 W with good linearity specifications. Thermal assessment from measurement results ensures transistors' durability.